IA Educativa: possibilidades e perspectivas para a prática docente - Nobre, Leonardo Braga (2024)
This work investigates the interactions between Artificial Intelligence (AI) and Education, highlighting the opportunities, impacts, and challenges in the teaching-learning process. Initially, it was planned to develop a website called "IA Educativa", but the approach was redirected to the creation of a practical and accessible booklet, aimed at educators and professionals in the educational field. The research conducted a comprehensive literature review, using databases such as WebScopus, CAPES platform, and Google Scholar, identifying and analyzing the main trends, gaps, and theoretical and practical contributions in the field of AI applied to Education. Furthermore, case studies and practical examples of the integration of AI tools and systems in educational contexts were examined. The main specific objectives include identifying research trends and gaps, examining how AI tools are being applied in education, building a theoretical basis on the evolution and pedagogical implications of AI, and developing a practical booklet that serves as a guide for the application of AI in education. The "IA Educativa" booklet offers a clear and practical view of the use of AI in education, covering from theoretical foundations to practical applications such as intelligent tutoring systems, adaptive assessments, interactive support, and educational data analysis. It also discusses ethical and privacy challenges associated with the use of AI, proposing future directions for research and practice. It is concluded that the booklet represents a significant contribution to educators, providing a valuable resource that facilitates the integration of AI technologies in the educational environment, promoting more personalized, efficient, and ethical teaching. The limitations include the need for periodic updates to keep up with rapid technological evolutions and the limited scope of the literature review. Future research may explore interactive digital versions of the booklet and the creation of complementary materials to expand its reach and effectiveness